Functional transformations of postnonclassical science in the information society - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article examines the transformation of the functions of science in the process of changing of the type of scientific rationality under the conditions of formation of Information society. The influence of socio-cultural factors on the functional transformation of post-nonclassical science is grounded.